Compliance of Patients Undergoing Hemodialisis with Recovery Time Post-Dialysis - Agustina, Fitriani; Yusra, Ainil; Taufiq, Said (Jurnal Keperawatan, 2024)
Post-hemodialysis, patients frequently experience symptoms that disrupt their comfort during daily activities, ranging from simple to strenuous tasks. Many hemodialysis patients do not feel well after dialysis sessions and require time to recover before resuming their usual activities at home or work. This study aims to determine the influence of fluid compliance, dietary compliance, and hemodialysis dose compliance on post-dialysis recovery time. A cross-sectional design with consecutive sampling was employed, involving 76 respondents. Data were collected by distributing questionnaires to patients undergoing hemodialysis during each session. Data analysis was conducted using the Mann-Whitney test with a 95% confidence interval. Post-dialysis recovery time ranged from a minimum of 15 minutes to a maximum of 1,800 minutes, with the majority of patients recovering within 240 minutes. There was a significant difference between post-dialysis recovery time and fluid restriction adherence (p-value = 0.000, p-value < 0.05), with respondents who adhered to fluid restrictions having a predominantly 45-minute recovery time. Similarly, a significant difference was observed between post-dialysis recovery time and dietary compliance (p-value = 0.000, p-value < 0.05), with respondents who adhered to their diet also having a 45-minute recovery time. Additionally, a significant difference was found between post-dialysis recovery time and hemodialysis dose compliance (p-value = 0.007, p-value < 0.05), with the majority of respondents adhering to the hemodialysis dose exhibiting a 120-minute recovery time. Post-dialysis recovery time is influenced by compliance to fluid restrictions, dietary management, and hemodialysis dosing in hemodialysis patients. Maintaining compliance to fluid restrictions, diet, and hemodialysis dosing can shorten post-dialysis recovery time.